KOLABORASI TRIPLE HELIX DALAM PENANGGULANGAN BENCANA TANAH LONGSOR DI KABUPATEN BUTON - Asmiddin Asmiddin; Anwar Sadat; Muh Askal Basir (Jurnal Manajemen Bencana (JMB), 2022)
Landslide disaster management policies and actions are then transformed into communities that experience vulnerability, so that the relationship between universities, companies, and the government in the field of disaster is very much needed in disaster mitigation efforts, especially landslides. The purpose of this study was to determine the triple helix collaboration in landslide disaster management in Buton Regency. This type of research is descriptive research with a qualitative approach. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies. The results of this study indicate that the minimal level of coordination and innovation that exists in the triple helix element so that no integration is created which makes mitigation efforts seem slow; between the elements of this triple helix has a different ideology, and this ideology is sometimes highlighted by each element of the helix, so that the triple helix relation cannot be built as desired; and conditions of bureaucratic procedures that are too difficult to make elements of universities and companies reluctant to collaborate with government elements in efforts to mitigate landslides in Buton Regency.